Development of a small-scale hydrogen liquefaction system - Garceau, Nathaniel Maurice; Baik, Jong Hoon; Lim, Chang Mu; Kim, Seo Young; Oh, In-Hwan; Karng, Sarng Woo (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
A liquid hydrogen (LH2) storage tank, vacuum jacketed transfer line, and hydrogen liquefier have been designed, built, and coupled together to form a small scale hydrogen liquefaction plant. The liquefier was designed to liquefy at 1 L/hr at 3 bar with a single stage Gifford-McMahon cryocooler. The liquefier can hold up to 200 L of LH2 in a multi-layer insulated (MLI) vacuum jacketed storage tank. The liquefier includes two ortho-para hydrogen (O-P) converters, a liquid nitrogen precooler and a heat pipe. After liquefaction, LH2 can be transferred to a 5 L storage vessel using a flexible, MLI and vacuum insulated low loss transfer line. This storage vessel was designed to limit boil-off by using two 1 m long G10-CR necks to reduce conduction, a radiation shield and MLI with high vacuum to reduce radiation and convective heat leak from the outer shell to the inner tank. Presented in this paper are more detailed system configurations and results of various operational modes and applications. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.